2012
DOI: 10.1210/jc.2012-1670
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tenascin C And Toll-Like Receptor 4 Levels in Visceral Adipose Tissue as a Link between Inflammation and Extracellular Matrix Remodeling in Obesity

Abstract: These findings indicate that TNC is involved in the etiopathology of obesity via visceral adipose tissue inflammation representing a link with ECM remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 51 publications
6
60
0
2
Order By: Relevance
“…In agreement with our findings, no differences in the expression of inflammatory genes in peripheral blood mononuclear cells between MHO and MAO groups were found in a recent study (33). In the same line, we found that TNC and MMP9, genes involved in matrix remodeling (21,30), were similarly upregulated in both obese groups, suggesting that VAT remodeling, as suggested by the expression of genes involved in this process, is analogously contributing to adipose expansion in both obesity phenotypes. To analyze the potential contribution of subcutaneous adipose tissue and, in particular, deep abdominal subcutaneous adipose tissue will be of interest in future studies.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…In agreement with our findings, no differences in the expression of inflammatory genes in peripheral blood mononuclear cells between MHO and MAO groups were found in a recent study (33). In the same line, we found that TNC and MMP9, genes involved in matrix remodeling (21,30), were similarly upregulated in both obese groups, suggesting that VAT remodeling, as suggested by the expression of genes involved in this process, is analogously contributing to adipose expansion in both obesity phenotypes. To analyze the potential contribution of subcutaneous adipose tissue and, in particular, deep abdominal subcutaneous adipose tissue will be of interest in future studies.…”
Section: Resultssupporting
confidence: 62%
“…The primer and probe concentrations for gene amplification were 300 and 200 nmol/L, respectively. All results were normalized to the levels of 18S rRNA (Applied Biosystems), and relative quantification was calculated using the DDCt formula (20,21). Relative mRNA expression was expressed as fold expression over the calibrator sample (average of gene expression corresponding to the lean group in VAT and MHO group in liver).…”
Section: Gene Expression By Real-time Pcrmentioning
confidence: 99%
“…We confirmed the ability of leptin to stimulate Tnf mRNA expression in murine 3T3-L1 adipocytes, but not in undifferentiated preadipocytes. Interestingly, our data revealed that leptin also promoted the synthesis and release of TNC, an endogenous activator of Toll-like receptor 4 (TLR4) that is key for the production of proinflammatory cytokines and ECM remodeling 19,22 . TNC expression can be induced in adipocytes after stimulation with proinflammatory cytokines and/or by growth factors from activated macrophages 11 , probably via TLR4 22 .…”
Section: Discussionmentioning
confidence: 90%
“…In line with this observation, our data showed that genes involved in the regulation of hypoxic response (Hif1a), inflammation (Tnf, Emr1), and excessive collagen deposition (Col6a1 and Col6a3) were highly enriched in EWAT of leptin-deficient ob/ob mice. Moreover, circulating levels and EWAT expression of the alarmin TNC were also significantly increased in ob/ob mice, contributing to the sustained inflammatory response and ECM remodeling associated to obesity 22 . Our results provide further evidence that in vivo chronic leptin administration reverted obesity, metabolic disturbances, as well as reduced the expression of hypoxic, proinflammatory and profibrotic genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation